2015
DOI: 10.1111/gbb.12202
|View full text |Cite
|
Sign up to set email alerts
|

Raphe serotonin neuron‐specific oxytocin receptor knockout reduces aggression without affecting anxiety‐like behavior in male mice only

Abstract: Serotonin and oxytocin influence aggressive and anxiety-like behaviors, though it is unclear how the two may interact. That the oxytocin receptor is expressed in the serotonergic raphe nuclei suggests a mechanism by which the two neurotransmitters may cooperatively influence behavior. We hypothesized that oxytocin acts on raphe neurons to influence serotonergically-mediated anxiety-like, aggressive and parental care behaviors. We eliminated expression of the oxytocin receptor in raphe neurons by crossing mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 59 publications
7
34
0
Order By: Relevance
“…Approximately, a fourth of serotonergic neurons in the dorsal raphe express OTR and, conversely, a third of OTR expressing neurons in the raphe are serotonergic. These neuroanatomical results are consistent with the observation that although OT acts in the raphe to reduce anxiety [22], this may not be due to OT action directly on serotonergic neurons because knocking out OTR from serotonergic cells had no effect on anxiety-like behavior [23]. These data suggest that OT's anxiolytic effects in the raphe may instead be coordinated by nonserotonergic neurons.…”
supporting
confidence: 85%
“…Approximately, a fourth of serotonergic neurons in the dorsal raphe express OTR and, conversely, a third of OTR expressing neurons in the raphe are serotonergic. These neuroanatomical results are consistent with the observation that although OT acts in the raphe to reduce anxiety [22], this may not be due to OT action directly on serotonergic neurons because knocking out OTR from serotonergic cells had no effect on anxiety-like behavior [23]. These data suggest that OT's anxiolytic effects in the raphe may instead be coordinated by nonserotonergic neurons.…”
supporting
confidence: 85%
“…They found that presynaptic OT receptors on dorsal raphe projections within the accumbens induce release of 5-HT and, further, that the activation of the post-synaptic 5-HT 1B receptors is necessary to establish social preference (Dölen et al, 2013). Another study used conditional knockout mice to demonstrate that male mice lacking the OT receptor on 5-HT neurons showed lower frequency of aggression than wild type mice; whereas female mice did not exhibit genotype effects on behavior (Pagani et al, 2015). This sex difference is important, but few other studies in mice have included female animals in their analyses.…”
Section: Interplay Between the Serotonin And Oxytocin Systemsmentioning
confidence: 99%
“…In women, OT increases the VTA activation to salient sexual and infant stimuli (Gregory et al 2015) in nulliparous and postpartum women, respectively. Finally, the raphe magnus shows a specific OT-ir innervation, from which OT can act on serotoninergic neurons (Eaton et al 2012;Mottolese et al 2014) modulating anxiety (Yoshida et al 2009) and aggression (Pagani et al 2015).…”
Section: Distribution Of Ot-immunoreactive Processesmentioning
confidence: 99%